Поняття та ознаки свтової валютної системи: міжнародно-правовий аспект - Шперун, Х. В.; Шперун, К. В.; Shperun, К. (My University, 2012)
The article is devoted to international legal problems of the global monetary system functioning. We consider the basic approaches to the defi nition of "global currency system", "International Monetary System" and other related concepts. The basic features of the global monetary system are determined. A key role in the regulation of international law issues arising in the course of world monetary system is indicated.
Шперун Х. В. Поняття та ознаки свтової валютної системи: міжнародно-правовий аспект /Х. В. Шперун // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України ; НУ ОЮА. – Одеса : Фенікс, 2012. – Вип.. 45. – С. 102-113.
Keywords: світова валютна система; міжнародно-правові проблеми функціонування світової валютної системи; міжнародна валютна система; міжнародне фінансове право; мировая валютная система; международно-правовые проблемы функционирования мировой валютной системы; международная валютная система; международное финансовое право; the world monetary system; International legal problems of functioning of the world monetary system; international monetary system; International Financial Law